2007
DOI: 10.1039/b605698a
|View full text |Cite
|
Sign up to set email alerts
|

Polarized measurements in Raman microscopy

Abstract: Driven by the demand to understand and quantify the macroscopic properties of highly anisotropic systems, polarized vibrational spectroscopy has emerged as a valuable technique in material and surface sciences as well as in technology and biophysical fields. Polarized Raman spectroscopy and its association with confocal optical microscopy is of particular interest to describe and understand the macroscopic properties of a naturally ordered sample or material that underwent external stress during processing or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…† The protocol for ascribing the electrical field vector distribution to the topography variations is described elsewhere. [25][26][27][28]46,47 Upon exposure of the polymer films to irradiation with AE451 interference patterns and the simultaneous acquisition of the topography development, the polarization was switched to the PP interference pattern, the position of irradiation change is marked by thick white arrows in Fig. 4.…”
Section: Reversible Switching Of the Polymer Film Topography During Changing Of Irradiation Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…† The protocol for ascribing the electrical field vector distribution to the topography variations is described elsewhere. [25][26][27][28]46,47 Upon exposure of the polymer films to irradiation with AE451 interference patterns and the simultaneous acquisition of the topography development, the polarization was switched to the PP interference pattern, the position of irradiation change is marked by thick white arrows in Fig. 4.…”
Section: Reversible Switching Of the Polymer Film Topography During Changing Of Irradiation Conditionsmentioning
confidence: 99%
“…When incoming light has a local electric field vector distribution/modulation in terms of either intensity or polarization, achieved by using, for instance, two beam interference lithography, the formation of local phases of aligned azobenzenes and their coupling to the polymer matrix result in anisotropic photo-mechanical stress large enough to induce macroscopic deformation of the polymer material. [26][27][28] Recently it was reported that the stress within the polymer material could be as high as several hundreds of MPa. 29,30 Large opto-mechanical stress generated within polymer films is manifested by local scission of covalent bonds when polymer chains are covalently attached to a solid surface.…”
Section: Introductionmentioning
confidence: 99%
“…31 In this case, polarized Raman spectroscopy can provide information about the symmetry of the vibration and hence can facilitate the assignment of spectral bands. Much work involving polarized Raman spectroscopy has been carried out in materials science on polymers, 30 nanowires, 32 and crystals. 33 34 wool and feather, 35 filamentous matters, [36][37][38][39][40][41] plant cell walls, 42 muscle, 43 bone, 44 and teeth.…”
Section: Theorymentioning
confidence: 99%
“…Such polarization measurements are of particular interest in revealing the crystallographic nature of materials. [6,7] However, in nanoscience applications, this limited spatial resolution excludes the precise characterization of individual objects or domains that are much smaller than the diffraction limit. In this context, tip-enhanced Raman spectroscopy (TERS), which employs a metallic tip scanning the near-field of the probed object, presents significant advantages that can lead to a better spatial resolution.…”
Section: Introductionmentioning
confidence: 99%